Galileo's dialogue - Malone, Adrian; Sutherland, Donald; Minor, Dale; LeBrun, Nancy; Corens, Kalindi; MacLowry, Randall (Discovery Channel, 1997)
This program tells the story surrounding Galileo's book from the revelation of the Copernican view that the sun, and not the earth, is the center of the universe to the trial of Galileo before the Holy Office. This drama pits egotistical visionary Galileo against the bullheaded Pope Urban VIII and science versus theology.